Re-irradiation for head and neck cancer: outcome and toxicity analysis using a prospective single institution database - Scolari, Chiara; Buchali, André; Franzen, Achim; Förster, Robert; Windisch, Paul; Bodis, Stephan; Zwahlen, Daniel R.; Schröder, Christina (Frontiers in Oncology, 2023)
Purpose Re-irradiation (re-RT) in head and neck cancer is challenging. This study prospectively explored the feasibility of re-RT in patients with loco-regionally recurrent or second primary head and neck cancer (LRR/SP HNC). Methods From 2004 to 2021, 61 LRR/SP HNC patients were treated with re-RT, defined as having a second course of RT with curative intent resulting in a cumulative dose of ≥100 Gy in an overlapping volume. Postoperative or definitive dynamic intensity-modulated and/or volumetric modulated re-RT was administered using twice daily hyperfractionation to 60 Gy combined with cisplatin or carboplatin/5-fluorouracil. Overall survival (OS), progression-free survival (PFS), locoregional control (LRC) and distant metastasis control (DMC) were analyzed and prognostic factors evaluated. Toxicity was prospectively recorded and graded. Results The median follow-up was 9.8 months. In 41 patients (67.1%), complete administration of the intended treatment was not feasible. In 9 patients (15%) re-RT was interrupted prematurely and in other 9, the complete re-RT dose was lower than 60 Gy, and 37 patients (61%) could not receive or complete chemotherapy. Two-year OS, PFS and LRC rates were 19%, 18% and 30%, respectively. 20 patients (33%) received the complete intended treatment, and 1- and 2-year OS rates were 70% and 47%, respectively. Charlson comorbidity index was an important predictor for treatment completion. Multivariate analysis revealed recurrent N stage 0–1, age, chemotherapy administration and re-RT dose of 60 Gy as prognostic factors for clinical outcomes. No grade 5 re-RT-related toxicity was observed. The most common new grade ≥3 acute toxicities were dysphagia (52%) and mucositis (46%). Late toxicity included grade ≥3 dysphagia in 5% and osteoradionecrosis in 10% of evaluable patients, respectively. 6 patients (10%) were alive after 9 years without progression and no late toxicity grade ≥3, except for 2 patients presenting with osteoradionecrosis. Conclusion Hyperfractionated re-RT with 60 Gy combined with platinum-based chemotherapy was a curative treatment option with acceptable toxicity in LRR/SP patients. Patients with higher comorbidity had a higher probability of failing to receive and complete the intended therapy. Consequently, they derived unsatisfactory benefits from re-RT, highlighting the importance of patient selection.